The Influence of Work Environment and Workload on Job Satisfaction of Employees of the Education and Culture Office of East Lombok Regency - Arya Aura Divayana; Thatok Asmony (CV. Abhinaya Indo Group, 2026)
This study aims to analyze the influence of the work environment and workload on the job satisfaction of employees of the East Lombok Regency Education and Culture Office. Work satisfaction inoptimality related to work environment conditions and workload variations are problems that need to be investigated further. The solution offered is to identify the most influential factors so that the agency can set improvement priorities. Data analysis was carried out by multiple linear regression method using SPSS 30 software. The results of the study showed that: (1) The work environment had a positive and significant effect on employee job satisfaction, as evidenced by a t-value of 6.630 and a significance of 0.000 (sig < 0.05); (2) Workload has a negative and insignificant effect on employee job satisfaction, with a calculated t-value of -0.182 and a significance of 0.856 (sig > 0.05). A determination coefficient (R²) of 0.531 indicates that the two independent variables together explain 53.1% variation in job satisfaction. This study concludes that the work environment is the main determinant factor of job satisfaction, while the workload that is classified as medium does not necessarily significantly reduce job satisfaction.